Unraveling the Effects of a Talimogene Laherparepvec (T-VEC)-Induced Tumor Oncolysate on Myeloid Dendritic Cells - Tijtgat, Jens; De Munck, Jolien; Dufait, Inès; Schwarze, Julia Katharina; Van Riet, Ivan; Franceschini, Lorenzo; Breckpot, Karine; Aerts, Joeri L.; Neyns, Bart; Tuyaerts, Sandra (Frontiers in Immunology, 2021)
T-VEC, a HSV-1 derived oncolytic virus, is approved for the treatment of advanced melanoma. The mechanisms that underly the systemic anti-tumor effect that is seen following intratumoral injection have not yet been studied but are likely to be mediated by myeloid dendritic cells (myDC) that initiate an adaptive immune response. In this study we could demonstrate that T-VEC is non-toxic for human myDC. T-VEC and a T-VEC oncolysate of melanoma cell lines were able to mature human myDC. myDC were able to take up lysed melanoma cells and cross-present melanoma-derived tumor antigens to antigen-specific T cells. Our results support the possible role of myDC as mediators of an adaptive anti-tumor effect and intratumoral co-administration of T-VEC plus autologous myDC could be a complementary treatment option. A clinical trial that investigates this hypothesis is currently ongoing.